Abby818
Abby818
08-11-2016
Mathematics
contestada
(1+sin y)(1+sin (-y))= cos^2y
Respuesta :
Аноним
Аноним
08-11-2016
Sin (-y)=-sin y
sin²y+cos²y=1 ⇒ cos²y=1-sin²y
Therefore:
(1+sin y)(1+sin(-y))=cos²y
(1+sin y)(1-sin y)=cos²y
1-sin²y=cos ²y
cos²y=cos²y
Answer: it is true this identity .
Answer Link
VER TODAS LAS RESPUESTAS ( 56+ )
Otras preguntas
What were the causes of WW1
what are manufacturing areas
Describe the range of a square root function
Evaluate the expression, using the given value of the variable. z ÷ 2 – 4z + 3(z – 3) when z = 8 A.
What is the stretchy storage bag in the digestive track
What is the definition of rendezvous
what are manufacturing areas
How did geography affect life in ancient china
5/6 - 1/6 = in simplest form
What is .03 as a percent and degree?